The Influence of Accountability, Transparency and Community Participation on the Management of Village Fund Allocations in Villages in Jambi District Outside the City of Muaro Jambi Regency - Nelda Afrita; Nela Safelia; Misni Erwati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to determine: (1) How community involvement, accountability, and transparency affect village budget distribution management in Jambi Luar Kota District villages concurrently. (2) How accountability affects village money distribution management in Jambi Luar Kota District communities. (3) The impact of openness on the administration of village budget distribution in the Jambi Luar Kota subdistrict's communities. (4) The impact of village fund allocation management and community involvement in Jambi Luar Kota District villages. Data from surveys and documents were used in this study to gather information on community engagement, accountability, and transparency. This study employed both primary and secondary data sources.